Krasny devitsy . Krasny devitsy . Beautiful Women . Красны девицы - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. A program for children and adolescents concerning health, fashion, cooking, and self-defense; an interview with Kristina Orbakaite. Featured in the program: Orbakaite, Kristina (Singer) Программа для детей и подростков, обсуждающая вопросы здоровья, моду, кулинарные рецепты, самооборону; интервью с Кристиной Орбакайте. В программе участвуют: Орбакайте, Кристина (Певица)